Neo-Historic Study of Qurat-ul-ain Haider’s Novel "Akhir-e-Shab kay Humsafar" - Alvi, Faiza Mazhar; Shah, Syed Ali Asghar; Awan, Muhammad Saqib Farooq (Makhz (Research Journal), 2023)
The beginning of modernism in Urdu literature was the end of 19th century. Modernism emerged as an ideology in social and literary life. This enlightenment project paved the way for the literary world to examine literature in different ways. Neo-historicism is one of these theories to examine literature in the light of history. It gives the special importance to the cultural element in understanding of literature. It sees not only the historical events in literature but also the cultural, political, language and social elements that drive it, expressed in literature. In this article theory of neo-historicism is being implemented on Qurat-ul-ain Haider’s Novel ’’Akhir-e-Shab kay Humsafar’’.